The Influence of Visual, Auditorial and Kinesthetic Learning Styles on the Learning Achievement of Cancer Fighting Children: Pengaruh Gaya Belajar Visual, Auditorial dan Kinestetik terhadap Prestasi Belajar Anak-anak Pejuang Kanker - Kafa, Satria Kharimul Qolbi (Pedagogia : Jurnal Pendidikan, 2022)
Cancer is a dangerous disease with a high mortality rate. From ancient times until now, cancer has various types of cancer of the blood, eye, bone and others. Every human being can get the disease regardless of age, starting from children to adults. Children up to adolescents are school children, so when a child is diagnosed with cancer, it will affect his education. Therefore, this study discusses the effect of visual, auditory, and kinesthetic learning styles on the learning achievement of those diagnosed with cancer as children cancer fighters. This research uses experimental methods through 3 types of styles with data sources of interviews, observation and documentation in the form of reports on teaching and learning activities. The data is processed by Anova Variant Analysis. From the results of these calculations, there are effects of visual, auditory, and kinesthetic learning styles on the learning achievement of children who fight cancer.